2014
DOI: 10.7567/jjap.53.071702
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on heterocharge accumulation in crosslinked polyethylene: Experiment and simulation

Abstract: This paper presents the pulsed electro-acoustic (PEA) measurement results of the space charge behavior in as-received and degassed crosslinked polyethylene (XLPE) plate samples. A modified bipolar charge transport model, taking into account the formation of ionic charges and the extraction barrier for electronic charges, is introduced to explain the origin of the observed heterocharge accumulation. The results show that in degassed sample, the formation of heterocharge at the anode is due to delayed extraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…8, where the charges obtained by the simulation and the experiment are both bulk charges inside the material and charges at electrodes have been eliminated. The little difference in the space charge in the middle of the material between simulation results and experiment results is due to the simplification of the charge transport model in simulation [3,13,14]. However, it can be seen that the simulation results are approximately in accordance with the experimental results, thus demonstrating the validity of the simulation model.…”
Section: Simulation Model and Verificationmentioning
confidence: 69%
See 2 more Smart Citations
“…8, where the charges obtained by the simulation and the experiment are both bulk charges inside the material and charges at electrodes have been eliminated. The little difference in the space charge in the middle of the material between simulation results and experiment results is due to the simplification of the charge transport model in simulation [3,13,14]. However, it can be seen that the simulation results are approximately in accordance with the experimental results, thus demonstrating the validity of the simulation model.…”
Section: Simulation Model and Verificationmentioning
confidence: 69%
“…where C is the extraction coefficient for the charge. The model parameters, which are shown in Table 2, are based on previous works [13,14], and some have been revised. To verify the accuracy of the simulation model, the simulation and experimental results are compared with the plane-parallel electrode, where the material in the plane-parallel electrode is the same as that in the needle-plane electrode.…”
Section: Simulation Model and Verificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The injection barrier height ranges from 1.1 eV to 1.27 eV. [18][19][20][21][22][23][24] The detrapping barrier height is in the range of 0.90 eV to 0.99 eV. 18-20.22-24 The magnitude range of the mobility value is 10 -16 m²V -1 s -1 to 10 -12 m²V -1 s -1 .…”
Section: Parameters Setting and Simulation Conditionsmentioning
confidence: 99%
“…However, several studies have found that the movement mechanisms of positive and negative space charges are different. [20][21][22][23] Specifically, the efficiency of injection, trapping, detrapping, and the migration speed are not exactly identical, which may lead to a remnant of space charge in the insulation after a period of voltage application. This is an important reason for the accumulation of space charge during the long-term operation of the cable.…”
Section: Fig 2 Accumulation Of Space Charges With Symmetricalmentioning
confidence: 99%